Handina mweya unotongwa nemadzinza: Perceptions and Reflections on the Stewardship of Musikavanhu through Guardian Spirits - Wonder Maguraushe; Elijah Chikomo (Ulster Institute for Social Research, 2023)
In traditional Shona culture and religion, dzinza (clan or lineage) is an identity of a clan. It is a notion that persists in many Shona families, where Christian and traditional religious ritual practices co-exist. We argue that identification with a particular lineage plays an overarching protective role in their lives, whether they believe in Chivanhu (African Traditional Religion) or Christianity. There are misconceptions about madzinza (lineages) amongst some members of the Christian community in Zimbabwe. Some gospel songs associate madzinza with evil spirits but in reality, madzinza signify a bond between people of the same lineage. This article examines the lyrics of Pastor Tsitsi Goba Kavhukatema’s song Handina mweya unotongwa nemadzinza (My soul is not controlled by lineage spirits) that explicitly state that madzinza only cause mishaps such as ailments, poverty and unemployment. We did a content analysis of the song text to extract the meanings portrayed in the song as gauged through lyrical content analysis. The textual analysis shows that the composer’s intended message is mired in a wrong perception of both the concept of madzinza and the role which they play amongst the living. The conclusion clarifies that what differs is the route to get to the destination of an everlasting life hence none of the two religions should impose itself on the other.